2020
DOI: 10.3126/forestry.v17i0.33634
|View full text |Cite
|
Sign up to set email alerts
|

Breeding seasonality of Chital (Axis axis) in the Hetauda Valley of Nepal

Abstract: Breeding seasonality of Axis axis differs from place to place mainly due to the difference in vegetation and climate. In Nepal, although Chital is found all over the lower Terai region, studies on breeding seasonality are limited. In this study, we observed the annual cycle of antler renewal and casting, monthly changes in frequency of bellowing call and ratio of new born fawn to adult and sub-adult females from October 2016 to March 2019. Seasonal peak of proportion of hard-antlered males was found in June an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…However, a previous study by Bhusal et al (2020) on the breeding patterns of chital in the forests of IOF revealed that the highest occurrence of fawning took place during December, January, and February, although fawning was observed throughout the year except in July and the peak breeding period was identified as May-June.…”
Section: Discussionmentioning
confidence: 81%
“…However, a previous study by Bhusal et al (2020) on the breeding patterns of chital in the forests of IOF revealed that the highest occurrence of fawning took place during December, January, and February, although fawning was observed throughout the year except in July and the peak breeding period was identified as May-June.…”
Section: Discussionmentioning
confidence: 81%
“…Given the frequency with which we recorded insect consumption and the abundance of (ignored) Trewia fruits at the time of the observations (which can be clearly seen in the videos), we suggest the insects provide an important nutritional requirement to the deer. As Trewia fruiting overlaps partially with fawning in chital (Bhusal et al, 2020), it is possible that insectivory is driven partly by a seasonal requirement for extra nutrition. Insects are rich in proteins and fats (Gasco et al, 2019), probably providing scarce nutrients for herbivorous deer.…”
Section: Discussionmentioning
confidence: 99%
“…Most of them are carried out in community forests while studies on national forests is lacking. The forest area of IoF supports 98 species of butterflies (Chhetri, 2017), 91 species of birds (Pokharel, 2017), and 11 species of snakes (Pradhan et al, 2020) and a population of spotted deer (Axis axis) (Bhusal et al, 2020). The study area is surrounded by human settlements on the north, east, and south sides, highlighting the urgent need for conservation intervention (Bajgain et al, 2020).…”
Section: Introductionmentioning
confidence: 92%